Deteksi dan Pengenalan Objek Dengan Model Machine Learning: Model Yolo - Qurotul Aini; Ninda Lutfiani; Hendra Kusumah; Muhammad Suzaki Zahran (CESS (Journal of Computer Engineering, System and Science), 2021)
Object recognition and detection have been in request by numerous parties since Computer Vision innovation within the 1960s, both within the industrial and medical area. Since then, many studies have focused on object recognition and detection with various types of algorithm models that can recognize and detect objects in an image. However, not all of these algorithm models are efficient and effective in their application. Most of the previous algorithm models have a relatively high level of complexity. Here, the author tries to explain and introduce the YOLO (You only look once) algorithm model, which has a high enough image detection processing speed capability and accuracy that can compete with the previous algorithm models. There are several advantages and disadvantages of each version made, which are explained in the discussion section.